A case study of whether South Africa's foreign policy with Zimbabwe and China is informed by its constitutional and international human rights obligations - Madima, Reshoketswe (Department of Public Law, 2020)
South Africa is a country that in the past has experienced gross human rights violations, and therefore has sought never again to have such violations. The government has sought to protect people's human rights by including them in the country's Constitution. Furthermore, South Africa has engaged with various international human rights bodies to further advocate for good human rights practices. However, the country has encountered some domestic challenges, with inequality and poverty being rife in the country. These challenges have implications for South Africa's economic foreign policy goals. This study explores South Africa's foreign policy with the Chinese government and the Zimbabwean government to explain why the country has chosen countries with poor human rights such as these. The research study will be centred around the period from 2008 to 2017. The offensive realism theory formed the theoretic framework of this research study. The study employed a qualitative research strategy as well as an interpretivist research paradigm. The findings show that when it comes to South Africa's foreign policy agenda, the government's goal is to establish a partnership with another country that will ultimately benefit the economic interests of South Africa, regardless of the country's human rights principles.